A Clinical Chronicle: The Use of Ventriculo-Atrial Shunt in Tuberculous Hydrocephalus Treatment - Abidin, Zainal; Lahdimawan, Ardik; Hosea, Nathania (Indonesian Journal of Case Reports, 2023)
Tuberculous meningitis (TBM) is the predominant bacterial meningitis form in children under 13, with an incidence of 8.6 per 100,000 before age 15. Tuberculous Hydrocephalus (TH), often presenting with hydrocephalus, poses a significant challenge in Indonesia for both children and adults. The commonly used Ventriculo-peritoneal (VP)-shunt procedure for TH, though prevalent, is associated with multiple complications. As an alternative, the Ventriculo-atrial (VA)-shunt procedure has been explored, but reports on its use in TH in Indonesia are lacking. This case report details a 1-year-old girl with TH who initially underwent a VP-shunt procedure, which proved unsuccessful. Subsequently, the VA-shunt procedure was employed, leading to a complete recovery. Our findings contribute valuable insights into the potential effectiveness of the VA-shunt as an alternative intervention for TH, especially in the Indonesian medical landscape.